2001
DOI: 10.1123/nirsa.25.2.48
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Security in Campus Recreation Centers

Abstract: Providing proper and adequate security is a critical element in comprehensive risk management for campus recreation facilities. However, little research has been done in this area to assess and analyze the status of security at campus recreation centers in the United States. The purpose of this study was to (a) examine the types of security systems used in campus recreation centers, (b) determine the most common types of security incidents that occur in these centers, and (c) examine facility security procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…This finding is supported by McGregor and MacDonald (2000), who recommended all activity supervisors/ instructors have basic first aid and CPR training. The current study's results were Veltri et al (2001), who reported that over half of campus recreation directors of recreational facilities throughout the United States required their staff to be certified in CPR and first aid. The 59% of campus recreation directors in this study who reported using CCTVs in their indoor facilities conveyed that the cameras were generally being used to monitor the facilities.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This finding is supported by McGregor and MacDonald (2000), who recommended all activity supervisors/ instructors have basic first aid and CPR training. The current study's results were Veltri et al (2001), who reported that over half of campus recreation directors of recreational facilities throughout the United States required their staff to be certified in CPR and first aid. The 59% of campus recreation directors in this study who reported using CCTVs in their indoor facilities conveyed that the cameras were generally being used to monitor the facilities.…”
Section: Discussionmentioning
confidence: 79%
“…Various forms of communication were found to be effective in helping to secure recreational facilities. During multiple events, two-way radios were the mode of communication most frequently used among staff (Veltri, Miller, & Scott, 2001). Readable signage used color to communicate and was placed in conspicuous locations as a means for facilities to communicate with the users (Tharrett, McInnis, & Peterson, 2007d).…”
Section: Communication Strategies and Surveillance Systemsmentioning
confidence: 99%
“…A great deal has been written in recent years in the professional and popular literature regarding risk management, legal liability, and participation in a wide variety of physical activities and sports. There have also been a number of publications and studies dealing with the need for risk management planning in a variety of institutions and organizations (Clement, 1988;Koehler, 1988;Lee, 1999;Mulrooney, Styles, & Green, 2002;McGregor & MacDonald, 2000;Miller, Veltri, & Gillentine, 2005;Miller & Veltri, 2003;Mulrooney & Green, 1997;Risk Management for Campus Recreation, 2007;Sharp, 1990;Stier, 2008;van der Smissen, 1990;Veltri, Miller, & Scott, 2001;White & Cardinal, 2003). However, there has not been a comparable contribution relative to the areas of risk management and legal liability in the area of collegiate/university intramural activities such as this research effort attempted to accomplish.…”
Section: Related Literaturementioning
confidence: 99%
“…Additionally, while limited recreational sport research exists discussing risk management as it pertains to accidents and liability, research discussing incident response/reporting and public safety measures is virtually nonexistent within the recreational sports canon. While a study conducted back in 2001 reviewed recreational sport security procedures (Veltri et al, 2001), such research has not been updated or expanded to include discussions of incident procedures and responses more generally. As such, this research provides a broad overview of campus recreational sport risk management practices.…”
Section: Introductionmentioning
confidence: 99%